Oral administration of the methanolic extract of Abutilon indicum (L.) Sweet seed proves effective in reducing cystic follicles and restoring the metabolic profile of Wistar albino rats with letrozole-induced polycystic ovarian syndrome - Rejuan Islam; Amlan Jyoti Ghosh; Supriyo Ghosh; Sagar Sarkar; Tilak Saha (Elsevier, 2024)
Background: Abutilon indicum(L.) Sweet, a member of the Malvaceae family, is widely distributed in China and is commonly known as Dong Kui Zi. In traditional Chinese medicine, it is extensively utilized in herbal formulations to address various health conditions, and the seeds of this plant have exhibited medicinal activities relevant to polycystic ovarian syndrome (PCOS). The current investigation aimed to provide a scientific foundation for assessing the efficacy of the methanolic extract derived from A. indicum seeds (AISE) on the ovarian and metabolic functions of rats, displaying letrozole-induced PCOS. Methodology: For this experiment, 30 Female Wistar rats were initially divided into five groups (n = 6), namely Vehicle control (VC), Low dose (LD), High dose (HD), Positive control (PC), and Negative control (NC). Four groups (LD, HD, PC, and NC) were treated with daily letrozole doses (0.5 mg/kg body weight) dissolved with 1 % Carboxymethyl cellulose (CMC) for 21 days for inducing PCOS. To assess PCOS induction, a daily examination of the estrus cycle and an Oral Glucose Tolerance Test (OGTT) were conducted on the 22ndday of the experiment. From the 22nd day, the LD and HD groups received daily oral AISE supplementation at 250 mg/kg and 500 mg/kg body weight (bw), respectively, for 28 days. Metformin (500 mg/kg) served as the PC treatment. After completion of the experimental duration, various assessments were performed to evaluate ovarian and metabolic functions. These included evaluations such as estrous cycle assessment, percentage of body weight gain, white adipose tissue (WAT) deposition, OGTT, measurement of testosterone levels, analysis of steroidogenic enzyme activity, examination of lipid profiles, assessment of oxidative stress profiles, and histopathological examinations. Results: Following 21 days of letrozole treatment, the rats exhibited irregular estrous cycles and elevated OGTT. However, after 28 days of treatment with AISE and metformin, the experimental HD group demonstrated restored estrous cycle irregularity, normalized body weight gain along with WAT deposition, normalized glucose tolerance, lipid profile, antioxidative parameters, and the reinstatement of healthy ovarian architecture compared to the vehicle control group. Conclusion: Administration of AISE restores regular ovarian function in consort with homeostatic metabolic parameters in female Wister rats with PCOS and oxidative stress. These findings support the traditional use of A. indicum and further research may lead to the development of an effective natural therapy for PCOS.